A reassessment of the pycnogonid genus Cheilopallene (Arthropoda, Callipallenidae) with description of a new species from Papua New Guinea - Staples, David A. (Zootaxa, 2015)
The genus Cheilopallene is reviewed. Three species are assigned to species incertae sedis pending further analysis. Specimens from Lizard Island, Queensland, previously identified as C. nodulosa are reassigned to C. brevichela. Suspected sexual dimorphism represented by the presence of a chelifore scape node in female C. nodulosa is supported by the finding of the same dimorphism in C. brevichela and in a new species from Milne Bay, Papua New Guinea. It is likely that the presence of a chelifore scape node is a diagnostic character of all females in the genus Cheilopallene. An amended diagnosis is provided.